Production and Quality Evaluation of Functional Burgers From Monodora myristica (Gaertn.) Dunal and African Breadfruit - Anna Ngozi Agiriga; Maduebibisi Ofo Iwe (University of Sultan Ageng Tirtayasa, 2024)
Functional burgers were produced from Monodora myristica-African breadfruit blends and toasted African breadfruit seeds. Flour was produced from Monodora myristica seeds and the flour was defatted. African breadfruit seeds were divided into two parts; the first was processed into flour after parboiling and dehulling, and the second was toasted and dehulled. Composite flour was produced from Monodora myristica and African breadfruit in the ratio of MA90:10, MA80:20, MA70:30, MA60:40, and MA50:50 respectively. 100% wheat flour (WF100) was the control. The toasted breadfruit seeds were coated with Monodora myristica-African breadfruit blends and baked. The control was African breadfruit seeds coated with 100% wheat flour (SWF100). The proximate composition, and functional properties of the blends; proximate composition, mineral content, and sensory properties of the burgers were all determined using standard methods. Data were statistically analyzed using SPSS version 20. The crude protein, fiber, ash, fat, foaming capacity, and emulsion capacity, of the blends increased as Monodora myristica level increased but carbohydrate reduced. The blends' water and oil absorption capacities increased as African breadfruit flour increased. The protein, ash, fat, fiber, phosphorus, magnesium, calcium, and iron content of burgers increased with increased inclusion of Monodora myristica flour and carbohydrate reduced. Burgers from WF100 had the least value in all the nutritional attributes analyzed but the highest carbohydrate. The composite burgers had superior nutritional properties than 100% wheat flour burgers. They also compared favorably with SWF100 in all the sensory attributes assessed. Burgers produced from MA60:40 were most preferred in terms of overall acceptability.